Common Denominators in the Immunobiology of IgG4 Autoimmune Diseases: What Do Glomerulonephritis, Pemphigus Vulgaris, Myasthenia Gravis, Thrombotic Thrombocytopenic Purpura and Autoimmune Encephalitis Have in Common? - Koneczny, Inga; Yilmaz, Vuslat; Lazaridis, Konstantinos; Tzartos, John; Lenz, Tobias L.; Tzartos, Socrates; Tüzün, Erdem; Leypoldt, Frank (Frontiers in Immunology, 2021)
IgG4 autoimmune diseases (IgG4-AID) are an emerging group of autoimmune diseases that are caused by pathogenic autoantibodies of the IgG4 subclass. It has only recently been appreciated, that members of this group share relevant immunobiological and therapeutic aspects even though different antigens, tissues and organs are affected: glomerulonephritis (kidney), pemphigus vulgaris (skin), thrombotic thrombocytopenic purpura (hematologic system) muscle-specific kinase (MuSK) in myasthenia gravis (peripheral nervous system) and autoimmune encephalitis (central nervous system) to give some examples. In all these diseases, patients’ IgG4 subclass autoantibodies block protein-protein interactions instead of causing complement mediated tissue injury, patients respond favourable to rituximab and share a genetic predisposition: at least five HLA class II alleles have been reported in individual studies to be associated with several different IgG4-AID. This suggests a role for the HLA class II molecules and specifically the DRβ1 chain for aberrant priming of autoreactive T-cells towards a chronic immune response skewed towards the production of IgG4 subclass autoantibodies. The aim of this review is to provide an update on findings arguing for a common pathogenic mechanism in IgG4-AID in general and to provide hypotheses about the role of distinct HLA haplotypes, T-cells and cytokines in IgG4-AID.